Pattern recognition of 5G device serial number using K-Nearest Neighbors (K-NN) machine learning algorithm - Sitorus, Zulham; Antoni, Robin; Limbong, Yohannes France; Sitompul, Jelly Rolley; Br Tarigan, Sella Monika (Jurnal Mantik, 2025)
5G networks are the latest generation of mobile communications technology that offer significant improvements in speed, capacity, and connectivity. However, along with the benefits it brings, it also brings a new set of challenges in the form of security breaches. Many 5G devices have been lost on-site. These devices are ABIA, AMIA, ASIB. Each of these devices has a serial number as identification data for each device. The rise of theft cases is due to the existence of collectors who are able to buy expensive stolen 5G devices for resale. So, the research will make the introduction of 5G device serial numbers using the Machine Learning (ML) with K-Nearest Neighbors (K-NN) algorithm. This pattern recognition is success to be done then become a guidance to recognizing stolen 5G devices. Next, this device cannot be used (deactivated) and be sold by system. This can break the demand and supply chain for stolen 5G devices. Based on the testing, there are 6 mismatches of 20 data testing or 70% data match